Carbon‐Based Electrocatalysts: Atomic Modulation and Structure Design of Carbons for Bifunctional Electrocatalysis in Metal–Air Batteries (Adv. Mater. 13/2019). Issue 13 (25th March 2019) - Huang, Yiyin; Wang, Yueqing; Tang, Cheng; Wang, Jun; Zhang, Qiang; Wang, Yaobing; Zhang, Jintao
Abstract : In article number1803800, advanced carbon electrocatalysts are addressed from the basic synthesis strategies to the fundamental understanding on electrocatalytic mechanisms. Qiang Zhang, Yaobing Wang, Jintao Zhang, and co‐workers put a special focus on the atomic modulation and structural design for bifunctional applications in metal–air batteries.